2020
DOI: 10.21608/adjg.2020.11248.1135
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance and Retention of Three Different Endocrown Materials

Abstract: Purpose: The purpose of the current study was to assess fracture resistance and retention of three different endocrown materials. Materials and Methods: Thirty (n=30) sound mandibular molars were endodontically treated and according to endocrown constructed material appointed arbitrarily into 3 groups (n=10 each); Group (1): IPS e.max CAD, Group (2): Vita Suprinity and Group (3): Vita Enamic. Samples of each group were additionally subdivided into2 subgroups (n=5 each) according to fracture resistance and rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The leather layers were used to reduce the possibility of endocrown fracture during tightening the upper compartment clips and to increase the friction between the two surfaces. UTM was set on pull-out mode with the speed of 5 mm/min, and the pull-out force was applied until complete separation of the restoration and the tooth [ 40 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…The leather layers were used to reduce the possibility of endocrown fracture during tightening the upper compartment clips and to increase the friction between the two surfaces. UTM was set on pull-out mode with the speed of 5 mm/min, and the pull-out force was applied until complete separation of the restoration and the tooth [ 40 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…When considering the restoration of the devitalized endodontically treated teeth, dental materials should be able to replace this loss of substance in order to guarantee mechanical and functional properties, esthetics and coronal seal (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The fracture resistance of the devitalized mutilated teeth is related to many factors including the root canal treatment (risk of vertical root fractures), coronal issues (quality and quantity of remaining tissues and loading context), the type, design and the material of the restorations used to restore these teeth whether the classical approach of post and core systems (post material and size, core material, ferrule effect) or endocrown adhesive restorations ( either butt joint designs or with shoulder finish line designs) (15) . Some in vitro studies reported that bonded all ceramic CAD-CAM endocrowns showed comparable fracture load values compared with conventional crowns.…”
Section: Discussionmentioning
confidence: 99%